Doing Business in Lao PDR : Constraints to Productivity - World Bank Group (World Bank, Washington, DC, 2018)
Overall, the investment climate seems to have deteriorated in Lao PDR between 2012 and 2016. In the 2012 survey, not one area of the investment climate was identified as a serious problem by more than 20 percent of firms. In the 2016 survey, there were six areas where more than 20 percent of firms identified areas of the investment climate as a serious problem. Although this could suggest a deteriorating investment climate, it might also reflect growing willingness to express opinions. Perceptions regarding the severity of main constraints also differ between various company types. For exporters, which are the companies that are best placed to expand and generate (job) growth in Lao PDR, informal practices of other firms (including other formal firms), tax rates, transportation, electricity, worker education, and trade regulations, are the areas identified as serious problems. Addressing these issues will be critical to support export-led growth in Lao PDR. This report also analyzes firm level productivity based on the data available and finds that Lao PDR’s enterprises are not productive compared to firms in neighboring countries. For example, the median level of labor productivity is lower in Lao PDR than in either Cambodia or Vietnam, and labor productivity in the most productive firms is significantly lower in Lao PDR compared to the other two countries; also, total factor productivity is generally higher in Vietnam than in Lao PDR. In addition, firms in Lao PDR also generally use significantly less capital than companies in Cambodia or Vietnam.